Analytic Preview of Spectral Contribution of the Neutrinos Emission from Deep Space during Specified Period: Analytic Preview of Spectral Contribution of the Neutrinos Emission - Naqvi, Syed Muhammad Ali Abbas; Afridi, Faisal Ahmed Khan; Jan, Bulbul; Zai, Muhammad Ayub Khan Yousuf; Baig, Mirza Jawad; Hussain, Arshad; Rashid, Syed Muhammad Haroon; Hussain, Abid (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
The earlier period investigations of Neutrinos emission from deep space indicate the existence of this particle which has been detected in various laboratories of the world. These laboratories are responsible for recording neutrinos emission originated from deep space. One laboratory situated near Sudbury, Ontario, Canada known as Sudbury Neutrino Observatory (SNO). Another laboratory is in Japan known as Kamikanado. We obtained a set of observations from both labs. It is obvious that the observations recorded at SNO have been utilized in this manuscript. From the same communication, the neutrino behaviour could be better understood by analyzing the SNO observed data set-I from November 1999 to May 2001 of D2O, while dataset-II is from July 2001 to August 2003 of salt water with particulars recorded, Run start Time since midnight. The samples used in this paper are 250 entries from both the observations sets. In this presentation, the most spectacular exhibition of the neutrino flux in its frequency components of the particles have been depicted in the form of a Periodogram that identifies covariance structure in the neutrino flux reaching this biosphere and parametric values obtained in this paper have been tabulated in various table frame of work. This communication does claim the neutrino emission characteristics in the real world. It has also been known from the literature survey that the same kind of work has not been framed in the third world countries where no neutrino detection laboratories exist. This piece of information will be beneficial for the private and public organizations where the experts are trying to explore deep space emissions detection and their characterization like the present study.